Effects of alum and addavax on immune responses and protection induced by ectodomain of influenza M2 protein displayed on nodavirus capsid - Ong, Hui Kian (2021)
Multiple copies of conserved ectodomain of matrix 2 protein (M2e) of influenza A virus (IAV) were genetically fused to the end of the C-terminal region of the capsid protein of Macrobrachium rosenbergii nodavirus producing chimeric proteins which assemble into virus-like particle (VLPs) displaying M2e-epitopes (NvC-M2ex3). Immunisation and virus challenges in BALB/c mice suggested that NvC-M2ex3 was indeed immunogenic and protective against lethal mouse-adapted A/PR/8/34 (H1N1) and A/HK/8/68 (H3N2) challenges. Nevertheless, previous studies lack mechanistic data that explain the protective effect of NvC-M2ex3. In addition, the effects of adjuvants on the immune responses and protection induced by NvC-M2ex3 remain elusive to date. Therefore, the objective of this study was to investigate the effects of two adjuvants, Alum and AddaVax on the immune responses and protection elicited by NvC-M2ex3 in BALB/c mice. Following immunisation, NvC-M2ex3 was shown to be well tolerated in animal, particularly when adjuvants were not involved in the formulation. Nevertheless, splenomegaly was observed in animal immunised with NvC-M2ex3 in the presence of Alum. No apparent morbidity was manifested in all mice immunised with NvC-M2ex3. Immunogenicity study indicated that antibody responses induced by NvC-M2ex3 were tailored by the adjuvants. AddaVax was demonstrated to induce a helper T-cell type 1 (Th1) skewed immune responses as supported by a higher IgG2a:IgG1 ratio and stronger Th1 cytokines profile, contrary to Alum. Immunophenotyping via flow cytometry analysis indicated that NvC-M2ex3 and adjuvants induced a CD4+ T-cell dominant response, higher macrophage but lower natural killer (NK) cell populations. Gene expression analysis of the mouse spleen via quantitative polymerase chain reaction (qPCR) suggested upregulation of T-cell related genes, corresponding to helper T-cell type 2 (Th2) and Th1 immunities induced by NvC-M2ex3 adjuvanted with Alum and AddaVax, respectively. Viral challenges indicated that NvC-M2ex3 conferred 100% protection against mouse-adapted H1N1 and H3N2 infections and reduced viral loads in the lungs and oropharynx of the mice. Co-administration of NvC-M2ex3 with adjuvants was demonstrated to be critical in improving morbidity in H1N1 but not in H3N2 challenges. All mice succumbed to the infection were shown to induce a CD8 T-cell dominant response which might contribute to immunopathology. Depending on the strains of IAV and adjuvants used, NvC-M2ex3 was shown to alter the splenic NK cell and macrophage counts differently. Gene expression study on the spleen of the mice challenged with H1N1 or H3N2 indicated that lower expression of genes associated with T-cell activation and cellular cytotoxicity correspond to improved disease outcomes. As a summary, NvC-M2ex3 induced protective immunity against IAVs and adjuvants were shown to improve protection against H1N1 infection. Although different adjuvants activated distinctive immune responses, both adjuvants contributed to protection against IAV challenges and ameliorated morbidity.